2019
DOI: 10.1016/j.isci.2019.04.031
|View full text |Cite
|
Sign up to set email alerts
|

An Oxa[5]helicene-Based Racemic Semiconducting Glassy Film for Photothermally Stable Perovskite Solar Cells

Abstract: Summary Attaining the durability of high-efficiency perovskite solar cells (PSCs) operated under concomitant light and thermal stresses is still a serious concern before large-scale application. It is crucial to maintain the phase stability of the organic hole-transporting layer for thermostable PSCs across a range of temperatures sampled during device operation. To address this issue, we propose a racemic semiconducting glassy film with remarkable morphological stability, exemplified here by a low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 42 publications
(52 reference statements)
0
29
0
Order By: Relevance
“…Helicenes are chiral; as a result, they are expected to have specific functionalities. Recently, helicenes have been widely applied in various fields [ 1 , 2 , 3 , 4 , 5 ], such as organic semiconductors [ 6 , 7 , 8 , 9 , 10 ], asymmetric catalysis [ 11 , 12 , 13 , 14 , 15 , 16 ], and molecular recognition [ 17 , 18 , 19 , 20 , 21 , 22 ], due to their diverse functionalities in materials. Many studies have also been reported on self-assembly phenomena at metal surfaces [ 23 , 24 , 25 , 26 ] caused by interactions with the π-orbitals of helicenes.…”
Section: Introductionmentioning
confidence: 99%
“…Helicenes are chiral; as a result, they are expected to have specific functionalities. Recently, helicenes have been widely applied in various fields [ 1 , 2 , 3 , 4 , 5 ], such as organic semiconductors [ 6 , 7 , 8 , 9 , 10 ], asymmetric catalysis [ 11 , 12 , 13 , 14 , 15 , 16 ], and molecular recognition [ 17 , 18 , 19 , 20 , 21 , 22 ], due to their diverse functionalities in materials. Many studies have also been reported on self-assembly phenomena at metal surfaces [ 23 , 24 , 25 , 26 ] caused by interactions with the π-orbitals of helicenes.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been extensively developed to improve the phase stability of CsPbI 3 including composition engineering ( Tian et al., 2020 ; Lau et al., 2019 ; Lu et al., 2020 ), crystallization regulation by introducing Lewis acid-base adducts ( Li et al., 2020a ; Nenon et al., 2018 ) or polymers ( Li et al., 2018a ; Jeong et al., 2020 ; Chen et al., 2019 ) into the CsPbI 3 precursor, surface capping treatments ( Wu et al., 2019 ; Wang et al., 2018 ), and dimension reduction by scaling down to quantum dots ( Bai et al., 2019 ; Sadeghi et al., 2020 ), nanocrystals ( Ghosh et al., 2018 ), or quasi two-dimensional (2D) films ( Qing et al., 2019 ; Zhang et al., 2017 ; Mauck and Tisdale, 2019 ; Liu et al., 2018 ). Among them, composition engineering by partly replacing Cs + with large organic cations can regulate the structural tolerance factor to improve the intrinsic phase stability of CsPbI 3 ( Xu et al., 2017 , 2019 ; Lee et al., 2021 ). The soft lattice of CsPbI 3 induced by its ionic bonding is favorable for a facile cation exchange to regulate the perovskite composition ( Deng et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…32 Recently we reported a racemic glassy lm composed of bis(4-methoxyphenyl)amine functionalized oxa [5] helicene (O5H-OMeDPA) as a donor-p-donor (D-p-D) type HTL for efficient PSCs. 33 Meanwhile, we are also curious to know whether a helicene based organic semiconductor is really superior to its planar counterpart. However the preparation of the perylo [1,12-bcd]furan (PEF) counterpart seems infeasible due to the lack of mature synthetic conditions for PEF.…”
Section: Introductionmentioning
confidence: 99%